Mesenteric Chylolymphatic Cyst of Terminal Ileum in a Child: A Case Report - Nandkishor Shinde; Mohammed Abdul Baseer; Abu Hasim Abdul Aziz; Sharana bassappa; Kakoli Paul Choudhary (RGUHS Journal of Medical Sciences)
Among mesenteric cysts chylolymphatic cyst is a rare one. Clinical presentation can range from asymptomatic to features of bowel obstruction. We encountered a case of a 4-year-old boy who presented with pain in the abdomen fever and vomiting for the past two days. On per abdominal examination a mobile soft mass measuring 10 X 9 cm was palpable in the right iliac fossa extending to the umbilical and right lumbar regions. Ultrasonography and CT of the abdomen revealed a cystic lesion in the right lower abdomen compared to small intestine. Intraoperatively a 15 X 10 cm cyst was found coming out of the terminal ileum mesentery adjacent to the ileal wall. Enlarged lymphatic vessels were observed entering the chylolymphatic cyst. Along with ileo-ileal anastomosis and removal of the affected ileal segment the chylolymphatic cyst was removed. The fluid inside the cyst was white and milky which is typical of a chylolymphatic cyst. Histopathological examination confirmed the diagnosis revealing lymphoid aggregates within the cyst wall. The postoperative period was uneventful.